Evaluation of a Salutogenetic Concept for Inpatient Psychosomatic Treatment. (16th September 2013) - Hinterberger, Thilo; Auer, Jochen; Schmidt, Stephanie; Loew, Thomas
Abstract : The increase of psychosomatic disorders due to cultural changes requires enhanced therapeutic models. This study investigated a salutogenetic treatment concept for inpatient psychosomatic treatment, based on data from more than 11000 patients of a psychosomatic clinic in Germany. The clinic aims at supporting patients' health improvement by fostering values such as humanity, community, and mindfulness. Most of patients found these values realized in the clinical environment. Self-assessment questionnaires addressing physical and mental health as well as symptom ratings were available for analysis of pre-post-treatment effects and long-term stability using one-year follow-up data, as well as for a comparison with other clinics. With respect to different diagnoses, symptoms improved in self-ratings with average effect sizes between 0.60 and 0.98. About 80% of positive changes could be sustained as determined in a 1-year follow-up survey. Patients with a lower concordance with the values of the clinic showed less health improvement. Compared to 14 other German psychosomatic clinics, the investigated treatment concept resulted in slightly higher decrease in symptoms (e.g., depression scale) and a higher self-rated mental and physical improvement in health. The data suggest that a successfully implemented salutogenetic clinical treatment concept not only has positive influence on treatment effects but also provides long-term stability.